Debates teóricos y metodológicos actuales sobre las políticas públicas - Antonio Camou (Coord.) (Estado y Política(s), 2017)
This publication arises as a result of an itinerary of research, reflection and collective debate that has already been shared for several years around the problems of the State, political processes and the development of public policies.